Fabrication of composite polymers with micron size copper and graphite additives in masked stereolithography - Kaya, Ali Can; Sandik, Mustafa Hakan; Temiztas, Birguel Ascioglu (SPRINGER HEIDELBERG, 2024)
Masked stereolithography makes the fabrication of complex parts more effortless and less expensive and enables high surface quality. We fabricated pure resin, flexible resin, resin-6.1-wt% graphite, and resin with Cu concentrations spanning from 5.5 to 15.5 wt% at different printing conditions. The structure was investigated with electron and light microscopes, and tensile testing of the printed sample was carried out. Resin temperature, post-curing temperature, and time are the dominating factors determining the strength of printed samples. Resin-Cu composite depicted a strengthening effect at 10 degrees C degrees resin and post-curing temperatures, but no strengthening effect was found for flexible resin-Cu composite at 20 degrees C degrees. Cu particles agglomerated, forming a density-graded composite; however, graphite particles distributed more homogenously in the parts. Increasing the graphite gradually reduces the composite strength. As a result, the mechanical properties of the composites are dominated by the interaction between the fillers and the matrix.
Keywords: 3D printing; Stereolithography; Composite; Polymer; Fabrication; Materials Science